Inspiratory muscle training in patients with obesity: a systematic review and meta-analysis - Caicedo-Trujillo, Saúl; Torres-Castro, Rodrigo; Vasconcello-Castillo, Luis; Solis-Navarro, Lilian; Sanchez-Ramirez, Diana; Núñez-Cortés, Rodrigo; Vera-Uribe, Roberto; Muñoz-Muñoz, Isabel; Barros-Poblete, Marisol; Romero, Juan Eduardo; Vilaró, Jordi (Frontiers in Medicine, 2023)
Introduction: Obesity is a chronic medical condition that affects, among others, the cardio-vascular and respiratory systems. Interventions for its treatment focus on sustained weight reduction and general health improvement, leaving respiratory management aside. Our ob-jective was to determine the effects of inspiratory muscle training (IMT) in patients with obesity. Methods: A systematic review was performed in Embase, Cochrane Library (CENTRAL), CINAHL, Web of Science, and PubMed/MEDLINE on June 26, 2023. Randomised clinical trials (RCTs), and quasi-randomised clinical trials investigating the effects of IMT in people with obesity were included. Selected studies were screened by two independent reviewers who extracted data and assessed the quality of the evidence. Results: The initial search returned 705 potential studies were included. Ultimately, eight studies met the criteria for eligibility and were included in the review. IMT improves physical capacity (six-minute walk test (6MWT): 44.5 meters, 95% CI: 30.5 to 58.5; p <0.0001) and the strength of the inspiratory muscles (maximal inspiratory pressure (MIP): -28.4 cmH2O, 95% CI: -41.9 to -14.8; p <0.0001) compared to the controls, without differences in the pulmonary function, body mass index (BMI) and metabolic parameters. Conclusion: IMT improves physical capacity and inspiratory muscle strength without significant changes in lung function, BMI, and metabolic parameters.